Analisis Perhitungan dan Pelaporan Pajak Reklame dan Pajak Parkir Pada Badan Pendapatan Daerah Kota Manado - Kuhon, Karina; Wangkar, Anneke; Mintalangi, Syermi (GOING CONCERN : JURNAL RISET AKUNTANSI, 2024)
Taxes are a source of state income that will be used to fulfill the interests of society. One source of regional income is regional taxes which are used to finance the implementation and development of regional government. This research ais to determine the suitability of the calculation and reporting of advertisement tax and parking tax at the Manado City Regional Revenue Agency with Manado City Regional Regulation Number 2 of 2011 concerning Regional Taxes which are currently in effect. The analytical method used in this research is a descriptive method by conducting field studies through observation, interviews and documentation. The results of the research show that the implementation of the calculation and reporting of advertising tax and parking tax at the Manado City Regional Revenue Agency is in accordance with Manado City Regional Regulation Number 2 of 2011 concerning Regional Taxes. Keywords : Advertisement tax, parking tax, regional tax, tax calculation, tax reporting